Comparative Genomics of Host–Symbiont and Free-Living Oceanobacillus Species. (1st May 2017) - Kumar Mondal, Anupam; Kumar, Jitendra; Pandey, Rajesh; Gupta, Shashank; Kumar, Manoj; Bansal, Gourja; Mukerji, Mitali; Dash, Debasis; Singh Chauhan, Nar
Abstract : Survival in a given environment requires specific functions, so genomic variation is anticipated within in individual taxonomic groups that exhibit a large diversity in lifestyles. In this study, we sequence and assemble the genome of Oceanobacillus faecalis strain HM6, a resident of the human gut. Using the genus Oceanobacillus and the HM6 draft genome sequence, we explore the functional requirements for survival in a symbiotic arrangement within the human gut, in contrast to free living in the environment. Comparative genomics of seven available Oceanobacillus complete genomes highlight a genomically heterogeneous group. Our analysis did not find strict phylogenetic separation between free-living and host–symbiont Oceanobacillus members. By comparing functional gene content between host-associated and free-living species, we identified candidate genes that are potentially involved in symbiotic lifestyles, including phosphotransferase genes, transporters and two component response regulators. This study summarizes genomic and phylogenetic differences in the Oceanobacillus genus. Additionally, we highlight functions that may be key for survival in the human gut community.